EMPLOYEES MOTIVATION AND TRANSITION OF ISO 9001 QMS TOWARDS TQM - Stanojeska, Marija; Minovski, Robert; Jovanovski, Bojan; Sajfer, Zvonko; Ćoćkalo, Dragan; Stanisavljev, Sanja (Journal of Applied Engineering Science, 2016)
Employees’ motivation enables improvement in the effectiveness of the implementation process of Total Quality Management (TQM). Orientation towards process and their control, without significant emphasis of the employees, generates problems with the team work and communication, failure to meet or delaying of deadlines, increasing the total costs etc. Employee motivation means incentive for their complete and dedicated inclusion in the operation that contributes towards improved quality implementation of the TQM practices in a shorter period of time. Although aforementioned aspects are treated in the literature, still, the influence of the employees motivation on the transition from ISO 9001 QMS towards TQM is almost not covered at all. In that direction, the main objective of the paper is to create a generalized conceptual model for considered transition. For that sake, identification of the influential factors of ISO 9001, TQM and employees motivation as well as their analysis and determination of the most influential factors is carried out. The final set of factors is used as initial set of variables for creation of generalized conceptual model. The model introduces the correlation dependencies between the variables of treated areas. The created conceptual model in the advanced research will serve as a basis for design of a dynamic SD model which will enable experimentation in direction of transition of ISO 9001 towards TQM practices depending on the motivation of employees.
Keywords: Transition; Employee Motivation; ISO 9001; TQM